Gene expression of estrogen receptor during different stages of pregnancy in rats model - Al-Babily, Enas O.; Al-Watar, Barra D. (Iraqi journal of veterinary sciences, 2026)
One essential organ that steroid hormones target is the uterus and ovaries. Many receptors mediate the effects of these hormones such as estrogen receptors ER. The objective of this research is to evaluate the gene expression of estrogen receptors ERα and ERβ in the uterus and ovary on different days of pregnancy, as well as in female rats that are not pregnant. The estrogen receptor's gene expression in the ovary along with the uterine of rats' females was analyzed using the real-time PCR technique and immunohistochemical expression (IHC) of ER alpha in ovary and uterus. Thirty adult female rats were allocated into five groups at random, each group has six animals. non-pregnant groups and groups of pregnant at one, seven, fourteen and twenty days of pregnancy. The ovaries and uterus were extracted from each animal, and Real-Time polymerase chain reaction (RT-PCR) analysis was applied to evaluate the estrogen receptors (ER) expression. The expression of the ERα gene increased significantly within seven and twenty days of pregnancy where as ERβ expression of this gene did not differ between the different days of pregnancy and the ovary of non-pregnant rats. In uterus ERα and ERβ expression significantly increased in twenty days of pregnancy. In conclusion, in both pregnant and non-pregnant rats, this study demonstrates that the ovary and uterine express the gene for the estrogen receptor Erα and ERβ, the gene for the ERβ is strongly expressed duringtwenty days of pregnancy in the uterus, ERβ in the ovary is highest expressed during the first and second half days of pregnancy.